Journal of metamorphic geology / Diachronous collision in the Seve Nappe Complex: evidence from Lu-Hf geochronology of eclogites (Norrbotten, North Sweden) - Fassmer, Kathrin; Froitzheim, Nikolaus; Janák, Marian; Strohmeyer, Merle; Bukala, Michał; Lagos, Markus; Münker, Carsten (Journal of Metamorphic Geology, 2021)
The collision of Baltica and Laurentia during the Caledonian Orogeny happened at c. 400–420 Ma. However, subduction and collision processes also took place before this main collisional phase and the tectonic history of these is still not fully resolved. The Seve Nappe Complex in Sweden has recorded these earlier phases. The Seve Nappe Complex in Norrbotten (North Swedish Caledonides) comprises four superimposed nappes emplaced by eastward thrusting (from base to top according to the conventional structural interpretation): Lower Seve Nappe, Vaimok, Sarek, and Tsäkkok Lenses. Eclogites occur in the Vaimok and Tsäkkok Lenses. The Vaimok Lens represents rocks of the Baltican continental margin intruded by Neoproterozoic dolerite dikes which were later eclogitized and boudinaged. By contrast, eclogites of the Tsäkkok Lens are former oceanic basalts associated with calcschists, possibly representing the ocean–continent transition between Baltica and Iapetus. Previous age determinations for eclogitization yielded various ages between c. 500 and 480 Ma, in contrast to younger (460–450 Ma) ages of ultra high-P metamorphism in the Seve Nappe Complex further south in Jämtland. Eclogites from the Vaimok (one sample) and Tsäkkok (three samples) lenses were dated using Lu–Hf garnet geochronology. Garnet from all samples shows prograde zoning of major element and Lu contents and yielded well-defined isochrons of the following ages: 480.4 ± 1.2 Ma (Vaimok); 487.7 ± 4.6 Ma, 486.2 ± 3.2, 484.6 ± 4.6 Ma (Tsäkkok). The ages from Tsäkkok are interpreted to date the burial of the Iapetus–Baltica ocean–continent transition in a west-dipping subduction zone around c. 485 Ma, and the age from the structurally deeper Vaimok Nappe the following subduction of the continental margin. Previously reported ages of 500 Ma and older are not supported by this study. The age difference between eclogites in the Seve Nappe Complex in Jämtland (c. 460–450 Ma) and Norrbotten (c. 488–480 Ma) may reflect the collision of an island arc with an ...